Tourist : a new theory of the leisure class - MacCannell, Dean, 1940- (Berkeley, California : University Of California, 2013)
In this classic analysis of travel and sightseeing, Dean MacCannel brings social scientific understanding to bear on tourism in the postindustrial age, during which the middle class has acquired leisure time for international travel
Modernity and the Production of Touristic Experiences -- Sightseeing and Social Structure -- The Paris Case: Origins of Alienated Leisure -- The Other Attractions -- Staged Authenticity -- A Semiotic of Attraction -- The Ethnomethodology of Sightseers -- Structure, Genuine and Spurious -- On Theory, Methods and Application.
Includes bibliographical references and index.
Keywords: Leisure; Tourism; Travelers